PM2.5 Induced Nasal Mucosal Barrier Dysfunction and Epithelial–Mesenchymal Transition to Promote Chronic Rhinosinusitis Through IL4I1-AhR Signaling Pathway - Yue Wang; Bowen Zheng; Panhui Xiong; Yijun Liu; Longlan Shu; Yang Shen; Tao Lu; Yucheng Yang (Toxics, 2025)
Environmental pollutants like PM2.5 contribute to chronic rhinosinusitis (CRS). The aryl hydrocarbon receptor (AhR), a contaminant sensor linked to tryptophan metabolites, is regulated by IL4I. However, how PM2.5 stimulation via IL4I1 influences AhR activation and CRS pathogenesis remains unclear. This study explored the IL4I1-AhR pathway in CRS using patient tissues, HNEpCs, and murine models. Methods included IHC, qRT-PCR, and WB under PM2.5 exposure, with further investigation into downstream effects on CYP1B1 and epithelial–mesenchymal transition (EMT). Significant upregulation of IL4I1, AhR, and CYP1B1 was observed in CRS tissues, with higher expression levels in CRS patients. Exposure to PM2.5 activated the IL4I1-AhR pathway, leading to decreased E-cadherin, increased N-cadherin and vimentin, and impaired nasal mucosal barrier function. In vitro experiments demonstrated that PM2.5-induced EMT in HNEpCs was mediated by IL4I1-dependent AhR activation. CH223191 reduced cell migration and EMT, while IL4I1 knockdown attenuated AhR activation and EMT marker expression. Murine models further confirmed that PM2.5 exacerbated nasal polyp formation and tissue remodeling via the IL4I1-AhR pathway. This study underscores the critical role of the IL4I1-AhR signaling pathway in PM2.5-induced nasal mucosal barrier dysfunction and EMT in CRS. IL4I1, as an upstream regulator of AhR, promotes EMT and nasal mucosal barrier disruption.